Exchange-coupling effect in hard/soft SrTb0.01Tm0.01Fe11.98O19/AFe2O4 (where A = Co, Ni, Zn, Cu and Mn) composites. Issue 6 (15th April 2020) - Algarou, N.A.; Slimani, Y.; Almessiere, M.A.; Güner, S.; Baykal, A.; Ercan, I.; Kögerler, P.
Abstract: In this study, series of hard/soft SrTb0.01 Tm0.01 Fe11.98 O19 /AFe2 O4 (where A = Co, Ni, Zn, Cu and Mn) composites were fabricated via a single-pot citrate sol-gel approach. The structure, morphology and magnetic properties of prepared composite samples were investigated via X-ray diffraction (XRD), scanning and transmission electron microscopes (SEM - TEM) and vibrating sample magnetometer (VSM). The XRD analysis of all composite samples showed the co-existence of both hard (Sr hexaferrite) and soft (spinel ferrites) ferrite phases with minor impurity. TEM micrographs displayed well-distinguished particles of SrM and AFe2 O4 with different symmetry. The magnetic M − H hysteresis loops were performed at room temperature (RT; T = 300 K) and low temperature (T = 10 K) using VSM instrument. The magnitudes of various magnetic parameters including saturation magnetization (Ms ), squareness ratio (SQR = Mr /Ms ), remanence (Mr ) and coercivity (Hc ) were determined. M − H loops revealed smoothed curves and the dM/dH versus H curves exposed only a single peak, indicating that the exchange-coupling effect was accomplished in one-step. Moreover, the various composites showed relatively high Ms, Mr, and Hc values. The obtained results revealed the occurrence of exchange-coupling effect among soft and hard magnetic phases. The magnetic properties of various hard/soft SrTb0.01 Tm0.01 Fe11.98 O19 /AFe2 O4 composites (where A = Co, Ni, Zn, Cu and Mn) were evaluated also by ZFC-FC magnetization measurements with respect to different soft phases. A peak temperature in ZFC curves occurred for various prepared composites. This peak is attributed to competition of the movement of magnetic domain walls and thermal activation. The present study offers a simple but efficient route for the fabrication of exchange-coupled nanocomposites with the chemical formula SrFe11.98 Tb0.01 Tm0.01 O19 /AFe2 O4 (where A = Co, Ni, Zn, Cu and Mn) having controllable magnetic properties. It was found that the SrTb0.01 Tm0.01 Fe11.98 O19 /CoFe2 O4 composite sample displayed the strongest exchange-coupling behavior among the different prepared composite products.